Active Aging, Health Literacy, and Quality of Life among Elderly in the Northeast of Thailand - Petcherut Sirisuwan; Surachai Phimha; Pannee Banchonhattakit (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Ageing populations are a global phenomenon public health concerns in developed and developing countries. Method: A cross-sectional study was conducted among 1,226 persons aged 60 and older using multistage stratified systematic sampling from twelve districts in four provinces of the Northeast of Thailand. Results: Overall, participants were female (62.97%), the average age was 70.28 ± 7.44 years, and the vast majority only completed elementary school (81.41%). Most commonly, participants did not work (40.86%). 49.27% of participants had moderate active aging (active aging index: AAI was 0.69). The majority (72.19%) of the sample had limited health literacy and 42.09% of participants had a good quality of life.Conclusion: Almost two-thirds of the elderly had active ageing in low to moderate levels, almost threequarters of the elderly had limited health literacy and less than half of the elderly had a good quality of life. Appropriate strategies on quality-of-life development project able to live with potential parallel with health management for promoting health literacy.